PENGGUNAAN LINK QR CODE SEBAGAI JEMBATAN ANTARA MEDIA CETAK DAN DIGITAL DALAM BUKU RESEP MASAKAN HARIAN MAMI - Blanca Fernanda Herman; Ixsora Gupita Cinantya (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
"Video has become a media that can greatly simplify guiding activities in this day and age. This is the reason for creating cooking videos to serve as a supporting media in designing Buku Resep Masakan Harian Mami, packaged with the use of QR Codes. The function of QR Codes in the design of this book is used as an intermediary media that connects readers to cooking tutorial video links available in each recipe. The design of Buku Resep Masakan Harian Mami by including video in the form of QR Code links on each recipe that is connected to the YouTube video link in the form of cooking stages aims for the effectiveness of using QR Codes as a digital media in printed recipe books. By integrating QR codes, recipe books can provide access to additional digital content such as video tutorials and cooking ingredients. Through this research journal, QR codes have been shown to significantly increase reader engagement, facilitate understanding of recipes, and encourage experimentation in the kitchen. The research method used in this design is the 5-phase design by Robin Landa, starting from the orientation stage, which is data collection to be used as a design brief (interviews, observations, literature studies), analysis, which is formulating problems from the results of observations, concept for determining the design concept that will be used to design, design the stage of realizing the design concept, and implementation the design stage is applied to the main media. The final result of this work is a printed recipe book measuring 17.6 x 25 cm containing simple recipes for beginners, equipped with QR Codes to enrich the information available to readers."